Hybrid switched-capacitor/switched-quasi-Z-source bidirectional DC-DC converter with wide-voltage-gain range for hybrid energy sources EVs - Zhang, Yun; Liu, Qiangqiang; Gao, Yongping; Li, Jing; Sumner, Mark (Institute of Electrical and Electronics Engineers, 2018)
In this paper, a hybrid switched-capacitor/ switched-quasi-Z-source bidirectional dc-dc converter is proposed for electric vehicles (EVs) with hybrid energy sources, which has a wide voltage gain range in the bidirectional energy flows. Compared with the traditional quasi-Z-source bidirectional dc-dc converter, the proposed converter only changes the position of the main power switch, and employs a switched-capacitor cell at the output of the high voltage side. Therefore, the advantages of the wide voltage gain range and the lower voltage stresses across the power switches can be achieved. The operating principle, the voltage and current stresses across the power switches and the comparisons with other converters are analyzed in detail. Furthermore, the parameter design of the main components, the dynamic modelling analysis and the voltage control scheme are also presented. Finally, the experimental results obtained from a 400W prototype validate the characteristics and the theoretical analysis of the proposed converter.